Periodic Operation of Reactive Distillation of Dehydrogenation of 2-Propanol - Goto, Shigeo; Hori, Kenta; Abella, Leonila C; Gaspillo, Pag-asa D (ASEAN Journal of Chemical Engineering, 2004)
The system of 2-propanoVacetone/hydrogen can be effectivelyprovided for a chemical heat pump cycle. This research focuses on the liquid-phase dehydrogenation of 2- propanol to produce acetone and hydrogen at low temperatures under boiling conditions. The acetone produced has been known to have an inhibition effect in the liquid phase. This research examined experimentally the dehydrogenation of 2- propanol in a reactive distillation column with periodic r tlse supply. The conversion of 2-propanol with periodic operation is higher than that with steady-state operation. This behavior can be explained by the acceleration of the reaction rate in the repeated vaporization steps of 2-propanol on the solid catalyst. When 2-propanol enters into the reaction part at the bottom of the column by periodic pulse, the solid catalyst repeats the wet and dry states. Thus, the resistance of mass transfer in the liquid phase and the inhibition effect of acetone both can be reduced. As a preliminary experiment, the reaction rate was measured in a batch reactor by changing the ratio of the moles of 2-propanol to the mass of solid catalyst. The optimum ratio was then found. The effect of pulse interval, feed rate, and the kind of solid catalyst on the conversion was investigated in the reactor with or without the reactive distillation part.